An Indonesian Version of Child Oral Health Impact Profile-Short Form 19 (COHIP-SF19): Assessing Validity and Reliability - Nuraini, Siti L.; Rahardjo, Anton; Maharani, Diah Ayu (UI Scholars Hub, 2021)
Previous surveys have indicated that the majority of Indonesian children have poor oral health. However, scant information is available on children’s oral health related quality of life (OHRQoL). The purpose of this study was to assess reliability as well as discriminant and convergent validity of Child Oral Health Impact Profile-Short Form 19 (COHIP-SF 19) Indonesian version. Methods: The Indonesian version of COHIP-SF 19 was developed according to the guidelines for the cross-cultural adaptation process. The instrument was tested among 529 children between 12 – 15 years old who were randomly selected from six junior high schools in Jakarta. The psychometric testing included internal consistency reliability, test-retest reliability, discriminant validity, and convergent validity. Results: Mean age of the participants was 13.3±0.9 years and 54% of the participants were female. The mean COHIP-SF 19 score was 57.8±8.8 and the median was 58 (range 27 – 75). The internal consistency and test-retest reliability was excellent for COHIP-SF 19 score with Chronbach’s alpha 0.83 and intra-class correlation coefficient 0.81. Children with active decay, untreated caries with pulpal involvement, and gingivitis had significantly lower COHIP-SF 19 scores (p-value ≤ 0.030). Correlation between COHIP-SF 19 score, subscale scores and clinical severity as well as self-rated general or oral health were very low to low (rs = 0.04 – 0.27, p-value ≤ 0.028), after adjustment for children’s age and gender. Conclusions: The Indonesian version of COHIP-SF 19 was successfully developed to be used as an OHRQoL instrument for Indonesian school-age children. The internal consistency, test-retest reliability, discriminant validity, and convergent validity of COHIP-SF 19 Indonesian version were confirmed.